2020
DOI: 10.1007/s10544-020-00530-3
|View full text |Cite
|
Sign up to set email alerts
|

Derma rollers in therapy: the transition from cosmetics to transdermal drug delivery

Abstract: Derma roller, a device rolled onto the skin to form micropores, is extensively used for cosmetic purposes. The pores thus created are utilized to either result in the induction of collagen production, leading to glowing and wrinkle-free skin or for permeating the applied formulations to the site of action within the skin. Recent studies have shown the benefits of using derma rollers for transdermal delivery of drugs. In the nascent stage, this approach paves a way to successfully breach the stratum corneum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 68 publications
0
29
0
1
Order By: Relevance
“… 66 Other devices, such as the dermastamp, a similar device that features a handpiece attached to a needle-studded block, has been used in outpatient settings. 68 Much more recently, automated microneedling stamp devices, such as the Dermapen, have come into favor for their increased safety and efficiency. 69–71 …”
Section: Microneedlingmentioning
confidence: 99%
“… 66 Other devices, such as the dermastamp, a similar device that features a handpiece attached to a needle-studded block, has been used in outpatient settings. 68 Much more recently, automated microneedling stamp devices, such as the Dermapen, have come into favor for their increased safety and efficiency. 69–71 …”
Section: Microneedlingmentioning
confidence: 99%
“…Cosmetic application of laser therapy is a well-known field of laser therapy which has attracted a great deal of attention in dermatology and related fields. 16 Various parameters of an applied laser should be optimized to achieve a suitable therapeutic tool. Laser wavelength and pulse duration are the two important properties in laser therapy.…”
Section: Cosmetic Applications Of Laser Therapy and Complicationsmentioning
confidence: 99%
“…When the stratum corneum is pierced with microneedles, the mechanoreceptors and nociceptors residing within the dermis are left intact. The pain felt by the patient upon microneedling is proportional to the microneedle length, i.e., the longer is the microneedle, the greater is the possibility to reach and stimulate nociceptors within the viable epidermis [39,40] .…”
Section: Painlessmentioning
confidence: 99%
“…Furthermore, several in vivo studies, in both humans [41] and animal models [43] , have demonstrated that microneedle penetration is associated with minimal bleeds. A clinical study conducted by Haq et al [39] (2009), compared the induction of skin puncture between microneedles and hypodermic needles. They found that the lesion induced and the microchannel formed by platinum-coated silicon microneedles demonstrated minimal skin trauma with a more rapid recovery rate (8-24 h) compared to that induced by hypodermic needles.…”
Section: Minimally Invasive and Small Lesion Sizementioning
confidence: 99%